New Challenges in Crime Victims Protection in Bulgaria (Discourse of Law and Administration, 2021)
The article explores the latest development of the legal regulation of crime victims protection in Bulgaria and some practical dimensions of the daily work of victim support organizations and institutions involved. Increased society victimization requires more effective legal actions and relevant compliance measures with the most advanced European and global standards. The Bulgarian legislator is trying to follow the best models in victim rights protection as it is an essential obligation of a member state of the European Union. However, some deficits and delays in the transposition of the recent European acts are observed. The implementation activities of the specialized state authorities and the non-governmental sector are critically analyzed. Recommendations to meet the new challenges and proposals for further actions for improved victim’s support are offered.